Leisure attitude scale in adolescents and young adults - Freire, Teresa; Fonte, Carla (Paidéia (Ribeirão Preto), 2007)
Nowadays, the leisure and its attitudes constitute an important issue in Social Psychology research. The aim of this study was to realize the adaptation of the Leisure Attitude Scale (Ragheb and Beard) for Portuguese individuals, including adolescents and young adults. This scale measures leisure attitude according to the three components (cognitive, affective and behavioural). A sample of 462 students (57.8% girls and 42.2% boys) with a mean age of 19.97 (standard deviation of 4.85). The results confirm the original scale. Validity measures of internal consistency and content validity in the total scale and in the three subscales (Cognitive, affective and behavioural). The scale is an adequate instrument to measure leisure attitudes in the Portuguese context.